PENGARUH LOCUS OF CONTROL, KOMITMEN ORGANISASI, TURNOVER INTENTION, SELF ESTEEM IN RELATION TO AMBITION, DAN TIME BUDGET PRESSURETERHADAP PERILAKU DISFUNGSIONAL AUDIT (STUDI EMPIRIS PADA KANTOR AKUNTAN PUBLIK DI BALI) - Diah Utari (Jurnal Ilmiah Akuntansi & Bisnis, 2016)
This research is motivated by the dysfunctional audit behavior conducted by an auditor in the audit process through the manipulation of data or evidence, fraud, and irregularities against the applicable audit standards. Dysfunctional audit behavior can be influenced by several factors such as locus of control, organizational commitment, turnover intention, self esteem in relation to ambition, and time budget pressure.The purpose of this research was to examine the effect of locus of control, organizational commitment, turnover intention, self esteem in relation to ambition, and time budget pressure on dysfunctional audit behavior. This research using purposive sampling method, and a sample of 50 respondents who work as auditors working in Public Accounting Firms in Bali listed in the Directory Institute of Indonesia Chartered Accountants (IICA) in 2016. This research uses primary data by spreading the questionnaire. Data were analyzed using multiple linear regression analysis were processing through statistical software.The results indicate that the locus of control, turnover intention, self esteem in relation to ambition, and time budget pressure has a positive and significant influence on the dysfunctional audit behavior, while the organizational commitment has a negative and significant influence on the dysfunctional audit behavior.